The new notion and classification of assemblies in Polish law - Kołaczkowski, Bartosz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The topic of this paper is the issue of the notion and classification of assemblies in Polish law, while its direct aim is to analyse and evaluate the regulations of the above issue after the changes introduced by the Act of 24 July 2015 on the Law of Assemblies (Dz.U. item 1485). The discussion is divided into two parts: the first is devoted to the investigation of the very notion of assembly, the second to the analysis of the topic of classification of assemblies – from the perspective of the form of decision of an administrative authority regarding the permissibility of holding the assembly. Following this criterion, assemblies are divided into ones which only require notification and the silent acceptance of the administrative organ, spontaneous assemblies which do not require notification, assemblies which require prior permission, and finally assemblies in the case of which it is necessary to agree on the time and place of holding the assembly with the operator of the road.